Social Media as Learning Tools: A Bibliometric Study of Educational Applications - Mu’aggil, Ince Muh Ruhuddin; Musrifa; Pido, Nur Wahidah Thayib (English Education Department, 2023)
The integration of social media into educational practices has emerged as a significant trend, influencing how students and educators interact with learning content. This bibliometric study investigates the growing body of research on social media as a learning tool, aiming to analyze publication trends, thematic focuses, and methodological approaches. Utilizing major academic databases such as SINTA and Google Scholar, the study reviews articles published over the past decade to map the landscape of social media in education. The analysis reveals a notable increase in research since 2020, with fluctuations in publication numbers indicating a dynamic and evolving field. Mixed-method approaches are prevalent, reflecting a comprehensive analysis of social media's impact. Research subjects primarily include students, with a strong focus on English as a Foreign Language (EFL). Data collection methods vary, with questionnaires being the most common instrument, although issues related to validity and reliability are noted. The findings highlight the broad applicability of social media in education, from enhancing engagement and communication to addressing challenges such as privacy and distraction. The study underscores the need for rigorous research practices and greater transparency in data collection to better understand and leverage social media's potential in educational settings. Overall, the study provides valuable insights into the current state of research on social media as a learning tool and offers recommendations for future research directions.